A comparative effect of various surface chemical treatments on the resin composite-composite repair bond strength - Shaloo Gupta; Abhishek Parolia; Ashish Jain; M Kundabala; Mandakini Mohan; Isabel Cristina Celerino de Moraes Porto (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this in vitro study was an attempt to investigate the effect of different surface treatments on the bond strength between pre-existing composite and repair composite resin. Materials and Methods: Forty acrylic blocks were prepared in a cuboidal mould. In each block, a well of 5 mm diameter and 5 mm depth was prepared to retain the composite resin (Filtek™ Z350, 3M/ESPE). Aging of the composite discs was achieved by storing them in water at 37°C for 1 week, and after that were divided into 5 groups (n = 8) according to surface treatment: Group I- 37% phosphoric acid, Group II-10% hydrofluoric acid, Group III-30% citric acid, Group IV-7% maleic acid and Group V- Adhesive (no etchant). The etched surfaces were rinsed and dried followed by application of bonding agent (Adper™ Single Bond 2. 3M/ESPE). The repair composite was placed on aged composite, light-cured for 40 seconds and stored in water at 37°C for 1 week. Shear bond strength between the aged and the new composite resin was determined with a universal testing machine (crosshead speed of 0.5 mm/min). Statistical Analysis: The compressive shear strengths were compared for differences using ANOVA test followed by Tamhane's T2 post hoc analysis. Results: The surface treatment with 10% hydrofluoric acid showed the maximum bond strength followed by 30% citric acid, 7% maleic acid and 37% phosphoric acid in decreasing order. Conclusion: The use of 10% hydrofluoric acid can be a good alternative for surface treatment in repair of composite resin restoration as compared to commonly used 37% orthophosphoric acid.